Severe hemorrhage in children with newly diagnosed immune thrombocytopenic purpura - Neunert, Cindy E. (American Society of Hematology, 2008)
Controversy exists regarding management of children newly diagnosed with immune thrombocytopenic purpura (ITP). Drug treatment is usually administered to prevent severe hemorrhage, although the definition and frequency of severe bleeding are poorly characterized. Accordingly, the Intercontinental Childhood ITP Study Group (ICIS) conducted a prospective registry defining severe hemorrhage at diagnosis and during the following 28 days in children with ITP. Of 1106 ITP patients enrolled, 863 were eligible and evaluable for bleeding severity assessment at diagnosis and during the subsequent 4 weeks. Twenty-five children (2.9%) had severe bleeding at diagnosis. Among 505 patients with a platelet count less than or equal to 20 000/mm(3) and no or mild bleeding at diagnosis, 3 (0.6%), had new severe hemorrhagic events during the ensuing 28 days. Subsequent development of severe hemorrhage was unrelated to initial management (P = .82). These results show that severe bleeding is uncommon at diagnosis in children with ITP and rare during the next 4 weeks irrespective of treatment given. We conclude that it would be difficult to design an adequately powered therapeutic trial aimed at demonstrating prevention of severe bleeding during the first 4 weeks after diagnosis. This finding suggests that future studies of ITP management should emphasize other outcomes.